Methanolic Extracts of Waru Leaves (Hibiscus tiliaceus L.) for Controlling Armyworms (Spodoptera litura F.) - Putri, Diah Asta; Saputra, Arib Cahyo (Universitas Ahmad Dahlan, 2021)
Botanical extracts have been reported as biopesticides, which act as antifeedants, insect growth regulators and repellents. As biopesticides, botanical extracts offer a more sustainable solution to pest control as chemical pesticides have a residual problem and are prone to pest resistance. The present study was conducted to evaluate the efficacy of waru leaves extract to control S. litura larvae in vitro conditions. The extract was prepared by maceration with methanol as a solvent. Third instar larvae of S. litura were randomly grouped into 6 treatments consisting of 0%, 3%, 6%, 9%, 12% and positive control (Lannate). Each treatment consisted of 3 replications. Leaf Dipping method was used in the treatment. Observations were made for up to 4 days. The parameters observed were changes in larval morphology, mortality, LC50 and LT50. Data were analyzed using One Way ANOVA (followed by LSD) and Probit analysis. The results showed that the highest activity of waru leaf extract was found at a concentration of 12%, which caused a mortality of 53% larvae. The LC50 value was at a concentration of 11.72%, and the LT50 value was 3.287. It can be concluded that the leaf extract has the potential to control S. litura larvae.